The effect of Neem and pawpaw leaves supplementation on blood profile of broilers (2012)
A total of 300 fourteen day old broilers were randomly divided into 4 treatments and replicated 5 times under completely randomized design to make 75 birds per treatment and 15 birds per replicate. Neem leaf meal (NLM) and pawpaw leaf meal (PLM) were prepared by air drying for 10 days. The birds were assigned to different treatment diets supplemented with the leaf meals and prepared as follows; T1 (0% NLM + PLM), T2 (0.5% NLM + PLM), T3 (1% NLM + PLM) and T4 (2% NLM + PLM). Except for packed cell volume (PVC), monophils, cosinophils and platelets, there were significant (P<0.05) differences in white blood cell (WBC), lymphocyte, haemoglobin (Hb) heterophils of birds on the treatment diets compared with the control. While total serum protein (TSP) and globulin in the control recorded significant (P<0.05) lower values compared with treatment 2, 3 and 4. Albumin, cholesterol, Aspertate, Transaminase (AST), Alanine Transaminace (ALT), Alanine phosphatase (ALP) showed no significant (P>0.05) differences.